Agora de aprendizaje y transformación de la madera Chanul (2021)
The project Agora of learning and transformation of wood is located in the Pacific region in the municipality of Guapi-Cauca; the problem is given according to the way of construction as it has left aside the native materials of the place, in which its inhabitants have no knowledge of the benefits of the material such as wood, one of them is the Chanul wood that in this municipality is present in much of the territory; Therefore, the hypothesis is posed: How to strengthen the preservation of the Chanul tree for the recovery of vernacular construction systems; supported by the technification for the implementation of this resource in the current construction?